The Ontology of Personhood: Distinguishing Sober from Enthusiastic Personalised Medicine. (May 2019) - Feiler, Therese
In light of the successful occupation of the term 'person' for Personalised Medicine, it is necessary to ask what different notions of personhood practically imply. This article examines two. The first is the reductionist molecular individual, embraced by PM enthusiasts. Here the person is a contradictory dividuum, oscillating between increased autonomy and a new, infantilising tech-paternalism. The second relies on a Christ-analogical distinction of two modes. The dramatic amplitude of personal absence-presence then unfolds throughout time. This provides the logic or spirit of the medical act. Drawing on the ethics of war, it will be recast as an arduous task of mending.